Lagune evaluation: an analysis of request strategies by UPM German learners - Chin, Safinur; Mamat, Roslina; Burkhardt, Jurgen M.; Farid, Farhana (Universiti Putra Malaysia Press, 2018)
This study aims to find out to what extent German Malaysian learners at UPM can perform request strategies and the influences of Lagune course books on learners' production of request strategies. This study also describes correlation between the acquisition of request strategies by German Foreign Language (GFL) learners and the content in Lagune course books. Data was collected from third, fifth and seventh semester undergraduate learners using a pragmatic tool which is written discourse completion task (WDCT) questionnaires in German language. In addition, three course books were evaluated qualitatively. To analyse the data, the head act response was categorized based on Trosborg (1995) request classification strategies model and modification devices taxonomy from Soler et al. (2005). The findings indicated that seventh semester learners produced a variety of strategies performance than third and fifth semester learners and the Lagune course books have strong influence towards the strategies performed by the learners. Hence, Lagune course books give strong impact to the acquisition of requisitive strategies on third year German languages learners.